Pembelajaran Kosakata Arab pada Siswa Madrasah Aliyah di Kabupaten Banyumas - Subur Subur; Syifa Wafirotul Khusna; Sutrimah Sutrimah; Rena Eriska Fitri; Farah Edhar Khaerunisa (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2021)
In Indonesian Muslim society, mastery of Arabic is very important to improve the quality of Islamic education. Arabic can be an effective tool for studying Islamic literature which contains many educational values. In Arabic learning activities, there are two important elements to be learned: grammar and vocabulary. This study aims to analyze the various methods used by teachers and students in improving Arabic vocabulary comprehension for Madrasah Aliyah students in Banyumas Regency. The data was collected through documentation, observation and interviews with the teachers and students. Data analysis is done through description. The results showed that there are many ways of learning vocabulary (mufradat) such as; pointing the objects from to show the vocabulary (ibra>z), demonstrating (tamsil), role playing (lu'bah ad-daur), mentioning antonyms (zikr al-mutadat), mentioning synonyms (zikr al-mutaradifat), association/collection (tada'il al-ma'ani), mentioning the origin of the sentence (al-asl) and its derivation (musytaqat), the teacher explains a vocabulary through something related words, repeating/multiplying the reading, looking for new vocabulary in the dictionary and translating activities. In learning Arabic, vocabulary comprehension or Mufradat still uses the conventional methods which causes the mastery of Arabic vocabulary (mufradat) less optimal.",